Control of velvetleaf (Abutilon theophrasti) at two heights with POST herbicides in Nebraska popcorn. (20th August 2020) - Barnes, Ethann R.; Knezevic, Stevan Z.; Lawrence, Nevin C.; Irmak, Suat; Rodriguez, Oscar; Jhala, Amit J.
Abstract: Velvetleaf is an economically important weed in popcorn production fields in Nebraska. Many PRE herbicides in popcorn have limited residual activity or provide partial velvetleaf control. There are a limited number of herbicides applied POST in popcorn compared with field corn, necessitating the evaluation of POST herbicides for control of velvetleaf. The objectives of this study were to (1) evaluate the efficacy and crop safety of labeled POST herbicides for controlling velvetleaf that survived S -metolachlor/atrazine applied PRE and (2) determine the effect of velvetleaf height on POST herbicide efficacy, popcorn injury, and yield. Field experiments were conducted in 2018 and 2019 near Clay Center, Nebraska. The experiments were arranged in a split-plot design with four replications. The main plot treatments were velvetleaf height (≤15 cm and ≤30 cm) and subplot treatments included a no-POST herbicide control, and 11 POST herbicide programs. Fluthiacet-methyl, fluthiacet-methyl/mesotrione, carfentrazone-ethyl, dicamba, and dicamba/diflufenzopyr provided greater than 96% velvetleaf control 28 d after treatment (DAT), reduced velvetleaf density to fewer than 7 plants m −2, achieved 99% to 100% biomass reduction, and had no effect on popcorn yield. Herbicide programs tested in this study provided greater than 98% control of velvetleaf 28 DAT in 2019. Most POST herbicide programs in this study provided greater than 90% control of up to 15 cm and up to 30 cm velvetleaf and no differences between velvetleaf heights in density, biomass reduction, or popcorn yield were observed, except with topramezone and nicosulfuron/mesotrione 28 DAT in 2018. On the basis of contrast analysis, herbicide programs with fluthiacet-methyl or dicamba provided better control than herbicide programs without them at 28 DAT in 2018. It is concluded that POST herbicides are available for control of velvetleaf up to 30-cm tall in popcorn production fields.